Analisis kemampuan guru dalam mengembangkan keterampilan berpikir kreatif menulis puisi pada peserta didik kelas IV SD - Galang Fathoni Bagus Setyadi; Retno Winarni; Anesa Surya (Didaktika Dwija Indria, 2022)
Abstract. 21st century life is viewed as a modernity era in various areas, one of which is education. The 21st century's role is one of the keys to success in advancing education in both academic and nonacademic areas. That success should be accompanied by competence mastered by the teacher. Teachers must have adequate competence because it is particularly important in determining the success of the objectives of education, especially in today's modern era, the pennogical competence alone is not enough. Teachers need to have ability in planning learning programs, ability to interact with learners or manage the teaching process, and doing assessment ability. The skills of the 21st century are those requiring 21-century educated people to be literate, be technologically gifted, be critical in mind and creative in mind, and be able to communicate or collaborate effectively. One skill a learner must master is creative thinking skills. Creative thinking skills are the mental faculties that a person USES to build new ideas and ideas, so in school learning how well the teacher emphasizes on developing creative thinking skills. Creative thinking skills are among the skills a learner needs. Creative thinking skills are expected to benefit the science of nation.